In vitro concentration dependent detection of creatinine: a surface enhanced Raman scattering and fluorescence study. Issue 113 (28th November 2016) - Gangopadhyay, Debraj; Sharma, Poornima; Nandi, Rajib; Das, Moumita; Ghosh, Surajit; Singh, Ranjan K.
Abstract : (a) SERS spectra and (b) fluorescence spectra of Jaffe complex showing consistent variation relatable to the concentration of CRN. Abstract : An attempt has been made to detect the concentration of creatinine in a very dilute aqueous solution in vitro on the basis of the Jaffe reaction, the commonly used reaction for clinical determination of creatinine concentration in blood serum or urine. For this various spectroscopic techniques viz. Raman spectroscopy, surface enhanced Raman scattering, UV-visible and fluorescence spectroscopy have been used. As a result of the Jaffe reaction using aqueous solutions of creatinine at different concentrations and picric acid and NaOH as reagents, a reddish orange colored Jaffe complex is produced. The concentration dependent SERS spectra of the Jaffe complex show gradual decrease in the intensity of ring deformation mode of creatinine on decreasing creatinine concentration. The concentration dependent absorption spectra of the Jaffe complex show changes in intensity in one of the absorption peaks characteristic of creatinine. The concentration dependent fluorescence emission spectra of the Jaffe complex show a blue shift in emission maxima on reducing the concentration of creatinine in the solution. The observed results suggest the possibility to detect the concentration of creatinine in a very dilute solution in vitro by SERS and fluorescence techniques and the application of these techniques in vivo might aid in a more specific and accurate determination of creatinine in serum or urine.